Constructing black economic empowerment in South African mining: Government v corporate discourse. Issue 4 (2nd October 2019) - Makgoba, Metji
ABSTRACT: By employing a critical discourse analysis and approaching BEE as an institutionalised discursive phenomenon, this article demonstrates how the South African government constructs clashing BEE discourses in its policy and legal documents because of its complex political and economic interests. Instead of tightening its discursive mechanisms to enforce BEE to address racial inequality, the government uses the 2010 Mining Charter to decontextualise, dislocate, and weaken its transformation and political agenda. This article reveals how this discrepancy and redirection enable mining corporations to undermine, (re)frame, (in)validate or reject certain aspects of BEE to meet their own corporate interests. As they formally respond to government mandates, these firms are able to build a defensive rhetoric. In particular, this has allowed mining firms to adopt an ahistorical discourse of race and blackness, which can be traced back to the Mining Charter, and yet displaces and deracialises the political objective of BEE. They displace and decontextualise BEE by framing the transformation agenda as a managerial concept and ahistorical development issue. This strategy enables these firms to maximise the symbolic appearance of compliance while using their managerial authority and rational to limit the political costs and impacts of BEE.